Postcolonial Action or Continuing Colonisation? The role of a Gubbah Lawyer in the Formation of Hybrid Indigenous Corporations - Angus Frith (Sortuz)
Academic research has a long history in Australia of working with Indigenous people, often with less than satisfactory results from Indigenous points of view. It is suggested that approaches and methods learned from professional legal practice with Indigenous people can provide some guidance for researchers working in this area. Lessons learnt from legal practice include the need for respectful engagement, and recognition that the practitioner is bound by Indigenous culture and law in his or her interactions with the Indigenous group. The application of postcolonial theory in these circumstances supports this approach. Accordingly, research with and for Indigenous people should allow for the expression of Indigenous law and culture. At the least, such research should involve proper communication, trust, engagement for the long term, giving up control, listening and respect.